2007
DOI: 10.1108/13527590710759847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of commitment, job involvement and teams on customer satisfaction and profit

Abstract: PurposeThis study seeks to examine customer satisfaction (CS), productivity, and profitability in terms of the organizational commitment (OC) and job involvement (JI) of company customer contact personnel. Additionally, the study aims to investigate the relationship between the OC and JI of customer contact personnel in team and non‐team structures.Design/methodology/approachA field design is used for testing the study's four hypotheses and for examining the relationships between the independent variables and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Expectancy theory, as developed by Porter and Lawler (1968), argued that a pay-forperformance system influences job satisfaction (Ferris, 1977;Igalens & Roussel, 1999), therefore suggested this research that Capital Structure relating to Members' Satisfaction. Emery & Barker (2007) concluded that the Organizational Commitment of contact personnel relates significantly to Customer Satisfaction, and Customer Satisfaction related significantly to departmental profit, thus appropriate with this research that Unit Business related to Members' Satisfaction, although Organization Commitment did not related significantly to profit. Deluga & Souza (1991) researched the positive relationship between supervisor leadership training skills and job satisfaction in law enforcement, but leadership training for supervisors and the resulting level of job satisfaction for subordinates is lacking.…”
Section: Training and Education And Members' Satisfactionsupporting
confidence: 50%
“…Expectancy theory, as developed by Porter and Lawler (1968), argued that a pay-forperformance system influences job satisfaction (Ferris, 1977;Igalens & Roussel, 1999), therefore suggested this research that Capital Structure relating to Members' Satisfaction. Emery & Barker (2007) concluded that the Organizational Commitment of contact personnel relates significantly to Customer Satisfaction, and Customer Satisfaction related significantly to departmental profit, thus appropriate with this research that Unit Business related to Members' Satisfaction, although Organization Commitment did not related significantly to profit. Deluga & Souza (1991) researched the positive relationship between supervisor leadership training skills and job satisfaction in law enforcement, but leadership training for supervisors and the resulting level of job satisfaction for subordinates is lacking.…”
Section: Training and Education And Members' Satisfactionsupporting
confidence: 50%
“…Job satisfaction is an important concern for employers as it is believed that satisfied employees are more likely to show up for work , have higher levels of performance and will stay with the organisation (Robbin, Decanzo & Coulter, 2010) [28]. Leadership [29] while considering the importance of job satisfaction summed it as an end state of feelings. Employees are therefore satisfied with leaders who are concerned, considerate and supportive of these desires than those who are either indifferent or critical towards their desires and needs.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…22 Likewise, the transformational leader uses intellectual stimulation encouraging subordinates to be proactive, creative, and innovative in their thinking. 41 If problems arise, leaders focus on ''what'' problems instead of ''who's to blame.'' 41 If problems arise, leaders focus on ''what'' problems instead of ''who's to blame.''…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…42 As a result, creative thinking is enhanced, which leads to greater product innovation and positive effects for their organizations. 41 40,43 As a result of this factor, the subordinate feels ''trust, admiration, loyalty, and respect toward the leader'' 25(p262) as followers have a sense that their leader is caring for their individualized needs.…”
Section: Transformational Leadershipmentioning
confidence: 99%
See 1 more Smart Citation